Analyses of multi-pion Hanbury Brown–Twiss correlations for the pion-emitting sources with Bose–Einstein condensation. (19th April 2018) - Bary, Ghulam; Ru, Peng; Zhang, Wei-Ning
Abstract: We calculate the three- and four-particle correlations of identical pions in an evolving pion gas (EPG) model with Bose–Einstein condensation. The multi-pion correlation functions in the EPG model are analyzed in different momentum intervals and compared with the experimental data for Pb–Pb collisions at s NN = 2.76 TeV . It is found that the multi-pion correlation functions and cumulant correlation functions are sensitive to the condensation fraction of the EPG sources in the low average transverse-momentum intervals of the three and four pions. The model results of the multi-pion correlations are consistent with the experimental data in a considerable degree, which gives a source condensation fraction between 16% and 47%.